Prove na yung (secx-cscx)/(sinx-cosx)=(cscx)/(cosx)
.
.
.
hint po long equation yung pinakasagot and using 8 fundamental identities
this is 8 fundamental identities
csc(θ) =
sec(θ) =
cot(θ) =
tan(θ) =
cot(θ) =
(sin(θ))2 + (cos(θ))2 = 1
1 + (tan(θ))2 = (sec(θ))2
1 + (cot(θ))2 = (csc(θ))2

1
use it to answer this identity

Answers

2014-09-30T02:27:50+08:00
 prove that  (sec x - csc x)/(sin x - cos)    =  csc x/cos x
     (sec x - csc x)/(sin x - cos x)
   = 1/cos x - 1/sin x =  ( sin x - cos x)/(sin x cos x)(sin x - cos x)
         cancelled   ( sin x - cos x)  what remains is
                             1/sin x cos x  =    1/sin x . 1/cos x
                                                   = csc x/cos x
0